Pengaruh Kompetensi dan Kompensasi terhadap Motivasi Serta Dampaknya terhadap Kinerja Pegawai pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Tanjungpinang - Anas, Azwar; Ginting, Ginta; Rizky Widokarti, Joko (Bahtera Inovasi, 2022)
This study aims to determine the effect of competence and compensation on motivation and their impact on employee performance at the Kjesyahbandaran and Port Authority, Tanjungpinang. The study was conducted through quantitative methods with a sample size of 68. Data obtained through questionnaires and analyzed descriptively and Partial Least Squere (PLS) analysis. The results showed that employee competence had a significant effect on work motivation, compensation had a significant effect on employee work motivation, employee competence had no effect on employee performance, compensation had a significant effect on employee performance, work motivation had a significant effect on employee performance. Indirectly, employee competence and compensation have a significant effect on employee performance through work motivation.